RSVP-SQoS : A Secure RSVP Protocol - Talwar, Vanish; Nahrstedt, Klara; Nath, Suman (ICME'01: IEEE International Conference on Multimedia and Expo, 2001)
Distributed multimedia applications require end-to-end quality of service (QoS) in order to be accepted and used. One approach to achieve end-to-end QoS is to provide end-to-end resource reservations. Resource ReSerVation Protocal (RSVP) is a unicast and multicast signalling protocal for setting up network bandwidtch reservation. In this paper, we propose a solution for securing RSVP messages in a flexible, efficient and scalable manner. Our solution extends the RSVP protocal with a scalable QoS protection, using hybrid hierarchical security approach. The RSVP messages go through two different protocol treatments- one within subnetworks and the other across subnetworks. We use delayed integrity checking within the subnetwork by sending feedback messages from the egress node. A stronger integrity and encryption check is made on messages sent across subnetworks. Our solution is thus an intermediate approach between the extremes of hop by hop authentication and the SDS/CD protocols and overcomes the drawbacks of the two protocols.